Genetic disruption of the cardiomyocyte circadian clock differentially influences insulin-mediated processes in the heart. (September 2017) - McGinnis, Graham R.; Tang, Yawen; Brewer, Rachel A.; Brahma, Manoja K.; Stanley, Haley L.; Shanmugam, Gobinath; Rajasekaran, Namakkal Soorappan; Rowe, Glenn C.; Frank, Stuart J.; Wende, Adam R.; Abel, E. Dale; Taegtmeyer, Heinrich; et al.
Abstract: Cardiovascular physiology exhibits time-of-day-dependent oscillations, which are mediated by both extrinsic (e.g., environment/behavior) and intrinsic (e.g., circadian clock) factors. Disruption of circadian rhythms negatively affects multiple cardiometabolic parameters. Recent studies suggest that the cardiomyocyte circadian clock directly modulates responsiveness of the heart to metabolic stimuli (e.g., fatty acids) and stresses (e.g., ischemia/reperfusion). The aim of this study was to determine whether genetic disruption of the cardiomyocyte circadian clock impacts insulin-regulated pathways in the heart. Genetic disruption of the circadian clock in cardiomyocyte-specific Bmal1 knockout (CBK) and cardiomyocyte-specific Clock mutant (CCM) mice altered expression (gene and protein) of multiple insulin signaling components in the heart, including p85α and Akt. Both baseline and insulin-mediated Akt activation was augmented in CBK and CCM hearts (relative to littermate controls). However, insulin-mediated glucose utilization (both oxidative and non-oxidative) and AS160 phosphorylation were attenuated in CBK hearts, potentially secondary to decreased Inhibitor-1. Consistent with increased Akt activation in CBK hearts, mTOR signaling was persistently increased, which was associated with attenuation of autophagy, augmented rates of protein synthesis, and hypertrophy. Importantly, pharmacological inhibition of mTOR (rapamycin; 10 days) normalized cardiac size in CBK mice. These data suggest that disruption of cardiomyocyte circadian clock differentially influences insulin-regulated processes, and provide new insights into potential pathologic mediators following circadian disruption. Highlights: Cardiomyocyte clock disruption differentially influences insulin signaling proteins. Cardiomyocyte clock disruption attenuates glucose utilization. Cardiomyocyte clock disruption attenuates autophagy. Cardiomyocyte clock disruption augments protein synthesis.